Optimalisasi Pengawasan Komisi Kejaksaan dalam Mengawasi Pelanggaran Kode Etik Kasus Korupsi pada Jaksa - Dina Aprilia Iswara (CV Rewang Rencang, 2020)
A Code of ethics is needed in the world of the profession as an effort to realize the implementation of guidelines or behavioral guidance that can maintain the honor of a profession. The code of ethics of the profession can develop into a culture in society. In Indonesia, the professional code of ethics is bound by regulation in accordance with the profession itself, including one of which is the code of ethics and behavior of the Prosecutor contained in the Attorney General's Regulation of the Republic of Indonesia Number PER-014/A/JA/11/2012 concerning the Prosecutor's Code of Conduct. The Prosecutor's Code of Conduct is a set of norms of the description of the Prosecutor's Code of Ethics, as a guideline of priority that regulates the behavior of prosecutors both in carrying out their professional duties, maintaining the honor and dignity of their profession and in conducting community relations outside the ministry. Like the code of ethics in general, the prosecutorial profession's code of ethics aims to prevent the occurrence of office crimes. But on the ground level, efforts to realize the prosecutor's professional code of ethics experience several obstacles including cases related to crime or abuse of office by certain prosecutors. In addition to normatively, the position of the prosecutor is not strictly regulated in the constitution, also because the organizational structure of the Prosecutor of the Republic of Indonesia itself is within the government environment. So it is not surprising that it becomes a loophole for prosecutors to commit professional crimes such as corruption. Then the solution that can be offered is to establish a mechanism of supervision of the prosecutor's profession called the Prosecutor's Commission which has a role such as the Judicial Commission that oversees the profession of judges. Restructuring is needed for the performance of the Indonesian Prosecutor's Commission with the supervision of behavior and performance, in addition to providing rewards to outstanding Prosecutors.